Political socialization and democratic beliefs change: a panel study of Chinese students studying in Taiwan. Issue 1 (2nd January 2017) - Wang, Chia-Chou
ABSTRACT: Does the experience of studying in Taiwan significantly enhance the degree to which Chinese students hold democratic beliefs? What are the factors that cause the change? By adopting a political socialization approach, a panel survey with Chinese students enrolled in short-term studies in Taiwan was conducted. The results indicated that 41.44% of the students showed no change in the degree to which they hold democratic beliefs, whereas the degree of democratic beliefs held reduced among 34.23% of the students and increased among 25.33% of the students. The regression model developed for this study can be used to explain 21.60% of the variance in the degree to which the students hold democratic beliefs. Six of the nine hypotheses tested are confirmed.